2016
DOI: 10.1101/076265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipocyte JAK2 Mediates Growth Hormone-Induced Hepatic Insulin Resistance

Abstract: For nearly 100 years, Growth Hormone (GH) has been known to regulate insulin sensitivity and risk of diabetes. However, the tissue governing the effects of GH signaling on insulin and glucose homeostasis remains unknown. Excess GH reduces fat mass and insulin sensitivity. Conversely, GH insensitivity (GHI) is associated with increased adiposity, augmented insulin sensitivity, and protection from diabetes.Here we induce adipocyte-specific GHI through conditional deletion of Jak2 (JAK2A), an obligate transducer … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…To directly address this, Cordoba-Chacon et al (47) used adipose explant cultures to demonstrate that aHepGHRkd had normal basal and stimulated rates of lipolysis. This is also consistent with our previously published results showing that GH does not affect basal lipolysis but instead specifically interferes with the ability of insulin to suppress lipolysis (19). Thus, without directly attending to high circulating GH levels present in aHepGHRkd mice via concomitant loss of adipocyte Ghr or global Gh disruption, it is premature to conclude that fatty liver and NASH resulting from loss of hepatocyte Ghr occurs via liver-autonomous means.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To directly address this, Cordoba-Chacon et al (47) used adipose explant cultures to demonstrate that aHepGHRkd had normal basal and stimulated rates of lipolysis. This is also consistent with our previously published results showing that GH does not affect basal lipolysis but instead specifically interferes with the ability of insulin to suppress lipolysis (19). Thus, without directly attending to high circulating GH levels present in aHepGHRkd mice via concomitant loss of adipocyte Ghr or global Gh disruption, it is premature to conclude that fatty liver and NASH resulting from loss of hepatocyte Ghr occurs via liver-autonomous means.…”
Section: Discussionsupporting
confidence: 91%
“…Females are relatively protected from metabolic dysregulation in both humans and mice, and this has been attributed to, among other sex-based differences, a preferential partitioning of FA toward ketogenesis over VLDL TAG production (60). Our studies here were a follow-up to previous work using hyperinsulinemic-euglycemic clamps (19,20), where the high degree of variability between female animals when using this technique presented a resource-based limitation for us. Therefore, females were not included in the current aging study because we have yet to definitely determine the state of insulin sensitivity in either JAK2L or JAK2LA female mice.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…FGF1 has powerful insulin synergistic actions and is synthesized and secreted from adipose tissues (50, 73). Importantly, a recent study in adipose tissue‐specific Jak2 knockout mice has revealed a marked increase in hepatic insulin sensitivity and postulated that this was a result of altered secretion of an adipose tissue factor (74). It is plausible that this factor is indeed FGF1 and that it acts in an endocrine manner to increase insulin sensitivity in the obese Ghr ‐391 −/− and Ghr −/− mice.…”
Section: Discussionmentioning
confidence: 99%